2013
DOI: 10.1097/mib.0b013e31828029dd
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Disease Behavior in Patients with Crohn’s Disease by MR Enterography

Abstract: MRI represents an excellent imaging modality to correctly assess the Montreal classification-based disease behavior in patients scheduled for bowel resection with Crohn's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 30 publications
2
22
0
Order By: Relevance
“…In addition, it is possible to draw conclusions about possibly present extraluminal complications, such as abscesses or fistulas, that can be missed by endoscopic methods or conventional radiological double-contrast methods [3, 18 -20]. MRE is also in excellent agreement with current clinical score systems such as the Montreal classification regarding the evaluation of the disease with respect to inflammation, stenosis, or perforating processes [21]. It is therefore suitable for representing the basic radiological examination for further decisions regarding medication-based or surgical treatment concepts.…”
Section: Key Pointsmentioning
confidence: 56%
“…In addition, it is possible to draw conclusions about possibly present extraluminal complications, such as abscesses or fistulas, that can be missed by endoscopic methods or conventional radiological double-contrast methods [3, 18 -20]. MRE is also in excellent agreement with current clinical score systems such as the Montreal classification regarding the evaluation of the disease with respect to inflammation, stenosis, or perforating processes [21]. It is therefore suitable for representing the basic radiological examination for further decisions regarding medication-based or surgical treatment concepts.…”
Section: Key Pointsmentioning
confidence: 56%
“…In a retrospective study comparing MRE and surgical findings on the evaluation of how MRE correctly diagnoses Crohn's disease behavior according to Montreal classification, Schill et al [19] found that the MRE diagnosis of an inflammatory mass had the lowest sensitivity and the lowest negative predictive value. Adhesions between bowel segments are often present in inflammatory mass; so adhesions might have played a role in this result.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with known chronic inflammatory bowel disease and acute abdominal pain, the same working group additionally showed that regular emergency CT for intestinal wall evaluation is sufficient and no additional MRE studies are necessary since an advanced finding is often present in these patients [51]. In a further study of the Regensburg group, it was able to be shown in patients undergoing bowel resection that MRE is an excellent imaging modality to correctly evaluate the Montreal classification of disease behavior [52]. The extent to which MRE can be used as an independent objective imaging method in the diagnosis and treatment of Crohn's disease was evaluated in an additional study [53].…”
mentioning
confidence: 89%